Cyclotrimerization of phenylacetylene catalyzed by a cobalt half-sandwich complex embedded in an engineered variant of transmembrane protein FhuA. Issue 30 (19th July 2018) - Thiel, A.; Sauer, D. F.; Mertens, M. A. S.; Polen, T.; Chen, H.-H.; Schwaneberg, U.; Okuda, J.
Abstract : An (η 5 -cyclopentadienyl)cobalt(i ) complex was covalently incorporated in an engineered variant of the β-barrel protein FhuA. The new biohydrid catalyst cyclotrimerized phenylacetylene to give regioisomeric triphenylbenzenes. Abstract : An (η 5 -cyclopentadienyl)cobalt(i ) complex was covalently incorporated into an engineered variant of the transmembrane protein ferric hydroxamate uptake protein component: A, FhuA ΔCVF tev, using a thiol–ene reaction. A CD spectrum shows the structural integrity of the biohybrid catalyst. MALDI-TOF of the segment containing the anchoring site for the cobalt complex Cys545 confirmed successful conjugation. This biohybrid catalyst catalyzed the cyclotrimerization of phenylacetylene to give a mixture of regioisomeric 1, 2, 4- and 1, 3, 5-triphenylbenzene in aqueous medium.